2014
DOI: 10.1155/2014/871735
|View full text |Cite
|
Sign up to set email alerts
|

GABABReceptors Expressed in Human Aortic Endothelial Cells Mediate Intracellular Calcium Concentration Regulation and Endothelial Nitric Oxide Synthase Translocation

Abstract: GABAB receptors regulate the intracellular Ca2+ concentration ([Ca2+]i) in a number of cells (e.g., retina, airway epithelium and smooth muscle), but whether they are expressed in vascular endothelial cells and similarly regulate the [Ca2+]i is not known. The purpose of this study was to investigate the expression of GABAB receptors, a subclass of receptors to the inhibitory neurotransmitter γ-aminobutyric acid (GABA), in cultured human aortic endothelial cells (HAECs), and to explore if altering receptor acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…In resting ECs, eNOS is primarily placed at cell membranes and in cytoplasm, and translocate close to the nucleus by agonists [ 45 , 46 ]. eNOS translocation leads to increase level of [Ca 2+ ]i in ECs [ 47 ]. It has been shown GABA B receptors which expressed in cultured human arterial ECs regulate the translocations of eNOS and level of [Ca 2+ ]i [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In resting ECs, eNOS is primarily placed at cell membranes and in cytoplasm, and translocate close to the nucleus by agonists [ 45 , 46 ]. eNOS translocation leads to increase level of [Ca 2+ ]i in ECs [ 47 ]. It has been shown GABA B receptors which expressed in cultured human arterial ECs regulate the translocations of eNOS and level of [Ca 2+ ]i [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…eNOS translocation leads to increase level of [Ca 2+ ]i in ECs [ 47 ]. It has been shown GABA B receptors which expressed in cultured human arterial ECs regulate the translocations of eNOS and level of [Ca 2+ ]i [ 47 ]. Furthermore, another study showed baclofen, agonist GABA B receptor, induced vasodilation of 50% of rat retina vessels, and that this vasodilation is inhibited by 2-hydroxysaclofen, the GABA B receptor antagonist [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral GABA B receptors directly induce vasodepression in the retina and in the pulmonary vascular bed (Kaye et al ., ; Hinds et al ., ). The mechanism underpinning these effects may be related to changes in calcium handling and/or nitric oxide production as evidenced by studies using cell culture systems (Wang et al ., ). Additionally, GABA B receptors are associated with renal‐induced elevations in BP (Donato et al ., ) tubular fibrosis and atrophy as well as attenuation of renal nerve‐induced noradrenaline release (Erdö, ; Fujimura et al ., ; Sasaki et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Two recent studies suggest that cultured endothelial and smooth muscle cells express GABA B receptors. 9,10 However, whether intact vessels also contain these receptors to a functional significant amount is unclear.…”
Section: Article See P 621mentioning
confidence: 99%
“…11 Homogenates of human aortic endothelial cells and human umbilical vein endothelial cells converted radiolabeled [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]glutamate into [1-14 C]GABA, and incubation of living human umbilical vein endothelial cells with [1-14 C]glutamate resulted in the release of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]GABA into the culture medium. Inhibition of GABA transaminase, which degrades GABA and, thus, limits the half-life of this amino acid, increased its release by ≈18%, whereas inhibition or siRNAmediated knockdown of GABA producing GADs decreased GABA release by ≈50%.…”
Section: Article See P 621mentioning
confidence: 99%